Implementasi Strategi Bauran Pemasaran Pertenakan Lebah di UMKM Madu Lebah Klanceng di Desa Talang Kabupaten Nganjuk - Arya Dharma Syahputra Handika; Muhammad Rizky Awwalul Ramadhan; Ayundha Evanthy (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
the marketing mix of beekeeping products applied to the Lanceng Honey Bee UMKM in Talang Village is still not effective so that sales are still not optimal. At the time of writing this was more focused on honey products which are the flagship product of the Lanceng Honey Bee MSME in Talang Village. This study used a qualitative method where the author made direct observations at the research location, namely beekeeping at the Klanceng Honey Bee UMKM in Talang Village. To obtain primary data, the authors visited beekeeping locations several times directly to obtain the secondary data, the authors conducted a literature search. The results of observations at the Klanceng Honey Bee UMKM in Talang Village show that the marketing channel applied is a simple marketing channel or a marketing channel at the lower level which only consists of Lawang Honey Picking Agrotourism as producers and consumers as customers of the product